Analisis Pengeluaran Energi Saat Pedaling Pada Rute Tanjakan Cabang Olahraga Balap Sepeda - Tini Martini; Arif Fajar Prasetiyo (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2023)
The aim of this research is to determine the results of the analysis of energy expenditure when pedaling on the uphill route of the bicycle racing branch. The research method used in this research is a correlational description with a population of ten cycling athletes. Sampling used a total sampling technique, where the entire population was used as a research sample, namely there were ten samples. The instrument in this research is to measure energy using VO2 Max, while to measure bicycle pedaling skills using a cycle dynamic instrument. The results of this research are that there is a correlation from the energy analysis when pedaling on the uphill route of the bicycle racing sport.